The Effect of Reflection Massage On Reducing Anxiety of Burning Patients: Literature Study - Yari, Yarwin; Erlina, Rita; Letari, Sri Agung; Wahyudin, M Didin; Handoko, Syahrul; Azzam, Rohman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
In an article search using 3 databases, each of which was found from the National Library of 204 search results, PubMed 364 search results and Google Scholar 951 search results. After disqualification related to the year of publication, namely the last 5 years and the selection of duplicate articles, 485 articles were obtained, and in the end, 9 articles that matched the criteria were obtained. From 9 articles that have been reviewed and found, most of the patients who experienced burns experienced anxiety, but with different degrees of anxiety. Based on the literature review from 9 research journals, it can be concluded that reflexology is very useful for reducing anxiety levels in patients with burns. Reflexology can be combined with several other interventions such as music therapy and aroma inhalation therapy